The Influence of Self-Compassion on the Psychological Well-Being of Orphaned Adolescents at the Roisussobur Sidoarjo Orphanage - M. Fakhry Asa Fazary; Erny Fitroh Nabila Muwafiqi (Universitas Islam Cordoba Banyuwangi, 2025)
The achievement of psychological well-being is always sought to achieve psychological well-being because it ispart of every human being's life goal. The same goes for teenagers living in orphanages. But sometimes in achievingit must face its own challenges. Self-compassion and ridho are one of the factors that affect psychological wellbeing. The purpose of this study was to examine the effect of self-compassion and ridho on the psychological wellbeing of orphanages at the Roisussobur Sidoarjo orphanage. Sampling used non-probability sampling with apurposive sampling technique with a total population of 43 people living in the orphanage, and the sample was 32orphans, orphans or orphans. Retrieval of data using a questionnaire (questionnaire) made via google form withthree scales, namely self-compassion which refers to Neff's theory (2003), ridho adapting from Rusdi (2017),psychological well-being adapting from Ryff (1989). The results of the study showed that there was an effect ofself-compassion and ridho on the psychological well-being of orphanage youth by 32.7%, which means that themore self-compassion and ridho possessed by orphanage adolescents, the more psychological well-being there isin the orphanage. However, psychological well-being in adolescents at the orphanage is more influenced by ridho.